Combination Therapy, a Promising Approach to Enhance the Efficacy of Radionuclide and Targeted Radionuclide Therapy of Prostate and Breast Cancer - Tyrillshall S. T. Damiana; Simone U. Dalm (MDPI AG, 2021)
In recent years, radionuclide therapy (RT) and targeted radionuclide therapy (TRT) have gained great interest in cancer treatment. This is due to promising results obtained in both preclinical and clinical studies. However, a complete response is achieved in only a small percentage of patients that receive RT or TRT. As a consequence, there have been several strategies to improve RT and TRT outcomes including the combination of these treatments with other well-established anti-cancer therapies, for example, chemotherapy. Combinations of RT and TRT with other therapies with distinct mechanisms of action represent a promising strategy. As for prostate cancer and breast cancer, the two most prevalent cancer types worldwide, several combination-based therapies have been evaluated. In this review, we will provide an overview of the RT and TRT agents currently used or being investigated in combination with hormone therapy, chemotherapy, immunotherapy, and external beam radiation therapy for the treatment of prostate cancer and breast cancer.